Protective Role of Testicular Hormone INSL3 From Atrophy and Weakness in Skeletal Muscle - Ferlin, Alberto; De Toni, Luca; Agoulnik, Alexander I.; Lunardon, Giorgia; Armani, Andrea; Bortolanza, Sergia; Blaauw, Bert; Sandri, Marco; Foresta, Carlo (Frontiers in Endocrinology, 2018)
Androgens are primarily involved in muscle growth, whilst disease-driven muscle wasting is frequently associated with hypogonadism. The Leydig cells of the testes also produce the peptide-hormone Insulin-like peptide 3 (INSL3). INSL3 displays anabolic activity on bone, a target tissue of androgens, and its plasma concentrations are diminished in male hypogonadism. Here we tested the role of INSL3 on muscle mass regulation, in physiological and pathological conditions. Studies on C2C12 cell line showed that INSL3, acting on his specific receptor RXFP2, promotes skeletal muscle protein synthesis through the Akt/mTOR/S6 pathway. Next, studies on Rxfp2-/- mice showed that INSL3 is required to prevent excessive muscle loss after denervation. Mechanistically, denervated Rxfp2-/- mice lacked the compensatory activation of the Akt/mTOR/S6 pathway and showed an abnormal ubiquitin-proteasome system activation. Lack of INSL3 activity resulted also in reduced contractile force. These findings underlie a role of INSL3/RXFP2 in protein turnover, contributing to muscle wasting in male hypogonadism.